The Effect of Rubber Mixing Process on The Curing Characteristics of Natural Rubber - Hasan, Abu; Rochmadi, Rochmadi; Sulistyo, Hary; Honggokusumo, Suharto (Makara Journal of Technology, 2012)
This research is aimed at studying the relationship between rubber mixing processes and curing characteristics of natural rubber. The curing characteristic analysis was carried out through a natural rubber formula having been masticated and mixed, followed by curing. As many as four mastication methods were finely applied; each respected four sequences of rubber mixing process. In the first method, rubber was masticated for 5 minutes and then rubber chemicals and carbon black N 330 were simultaneously added. In the second and the third methods, rubber was masticated for 1 minute and then carbon blacks and rubber chemicals were also simultaneously added but using different type of fillers. In the fourth method, rubber was masticated for 3 minutes and then rubber chemicals and carbon black were subsequently added. The additions of rubber chemicals and carbon blacks to the masticated rubber were distinguished by the sequence and time allocated for each mixing process. The carbon blacks were added in two stages by which 10 phr was added first and the remaining 40 phr was added later along with oil. In another method, ratios of the carbon blacks addition (as done in the first and the second stages) were 20:30, 30:20, and 40:10. The examination results showed that rubber mixing process gave an impact on the changes of curing characteristics. They were much affected by the method of carbon black addition. The mixing temperature also had an effect on both curing time and curing rate in which the higher the mixing temperature, the lower the curing time and curing rate. Vulcanization temperature also affected the curing time and curing rate in which the higher the vulcanization temperature, the lower the curing time and the higher the curing rate. Lastly, particle size of carbon black also gave an impact on the curing time and curing rate in which the smaller the particle size, the lower the curing time and the higher the curing rate.